A Study on the Relationship between Student’s Listening Anxiety and Listening Comprehension - Desi Surlitasari Dewi; Megawati Megawati (English Department, University of Riau Kepulauan, Batam,Indonesia, 2018)
The study was intended to investigate the relationship between listening anxiety and listening comprehension of high school students in Batam. This research was a correlational research that aimed to obtain the relationship between two variables, listening anxiety and listening comprehension. The data were collected by using two techniques, questionnaire, which was distributed to find out students’ listening anxiety level, while to find out students’ listening comprehension, a listening test was conducted. The data was analyzed by using Pearson Product-Moment correlation to obtain the degree of relationship between two variables (listening anxiety and listening comprehension). The finding of the research was that robtained was -0,287 that means: (1) there was a negative correlation between listening anxiety and listening comprehension; (2) the correlation degree between listening anxiety and listening comprehension was low; (3) there was no significant correlation between listening anxiety and listening comprehension, as robtained (-0,287) is smaller compared to rtable (0,374) .